The Role of the Inspectorate in Supervising Surface Water Tax: Case Study of the Inspectorate of West Papua Province - Roy Matasik; Priyo Hari Adi (GoAcademica Research & Publishing, 2023)
This study aims to analyze the role of the provincial inspectorate in supervising local taxes, especially the surface water tax. The method used in this research is descriptive qualitative method. to find out and analyze the role of the provincial regional inspectorate and its capabilities in conducting guidance and supervision on local taxes. Data The type of data used is primary data and secondary data. The technique used to analyze the data is to focus the data on the role of the provincial regional inspectorate and its capability in conducting guidance and supervision of regional tax supervision, especially the Surface Water Tax. Based on the results of research by the Inspectorate of West Papua Province, they have carried out their main tasks properly and are in accordance with applicable regulations. However, it has not been effective in carrying out regional tax supervision. This is because there is no SOP related to tax oversight and a lack of human resource competency. Even though the SOP for supervising regional taxes does not yet exist, the implementation of supervising local taxes, specifically the surface water tax, is still carried out by following the procedures for general supervision and inspection.